2023
DOI: 10.1308/rcsann.2022.0050
|View full text |Cite
|
Sign up to set email alerts
|

Does titanium cage subsidence affect clinical outcomes in ACDF surgery? A tertiary centre experience

Abstract: Background Cage subsidence after anterior cervical discectomy and fusion (ACDF) surgery has been well documented with rates of up to 40%. Cages fill the void after cervical discectomy and promote fusion. These materials have different biomechanical profiles with differing rates of subsidence. This retrospective cohort study aimed to determine subsidence rates specifically associated with the novel Emerging Implant Technologies (EIT) titanium cage, identify risk factors associated with subsidence, and evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…30 However, further research is needed on this topic. Furthermore, while studies have found no correlation between subsidence of intervertebral cages and clinical outcomes, 3,5,7,8 one prospective randomized controlled trial performed by Kast et al 9 in 2009 concluded that subsidence of PEEK cages significantly correlated with poorer patient outcomes as measured by Odom's criteria. The current literature may not fully encompass the true effect of subsidence on clinical symptoms due to many studies reporting short-term follow-up less than 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 However, further research is needed on this topic. Furthermore, while studies have found no correlation between subsidence of intervertebral cages and clinical outcomes, 3,5,7,8 one prospective randomized controlled trial performed by Kast et al 9 in 2009 concluded that subsidence of PEEK cages significantly correlated with poorer patient outcomes as measured by Odom's criteria. The current literature may not fully encompass the true effect of subsidence on clinical symptoms due to many studies reporting short-term follow-up less than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is needed on this topic. Furthermore, while studies have found no correlation between subsidence of intervertebral cages and clinical outcomes [ 3 , 5 , 7 , 8 ], one prospective randomized controlled trial performed by Kast et al [ 9 ] in 2009 concluded that subsidence of PEEK cages significantly correlated with poorer patient outcomes as measured by Odom’s criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation